Trinidad and Tobago. Significant Achievements 2023 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2024)
In Trinidad and Tobago in 2023, a series of initiatives carried out by the Inter-American Institute for Cooperation on Agriculture (IICA) stands out, in collaboration with various institutions and partners, to meet national development objectives related to agriculture, food security, climate resilience and community development. Among the actions carried out are the training of more than 200 stakeholders in the protection of livestock against disease outbreaks, especially African Swine Fever (ASF) and salmonella, through webinars, technical meetings and facilitation in global frameworks that promote solutions for transboundary animal diseases. Strengthening the procedures and capacities of the Ministry of Agriculture, Land and Fisheries (MALF) to improve crop health, especially in the identification of nematodes and pest and disease surveillance. Supporting farmers and food processors to ensure food security from farm to market, especially in supply to the School Feeding Programme. Training and support for small and medium-sized agricultural businesses to improve their competitiveness and access to markets. Adopting nature-based solutions to address climate challenges, such as controlling soil erosion with vetiver grass. Improving the capacity of the public and private sector to measure and report greenhouse gas emissions related to agriculture. Promoting youth participation in agriculture and raising awareness about climate change among young people and teachers. And the establishment of inter-institutional dialogues to promote collaboration in rural and agricultural development projects.